Réponses

2014-05-10T10:03:56+02:00
1) D = 36-(3x+5)²
    D = 36-[(3x)
²+2*3x*5+5²]
    D = 36-(9x²+30x+25)
    D = -9x²-30x-25+36
    D = -9x²-30x+11

2) D = 36-(3x+5)²
    D = (6)²-(3x+5)²

Cette expression est de la forme a²-b² avec a = 6 et b = 3x+5
Rappel : a²-b² = (a+b)(a-b)

   D = (6+3x+5)[6-(3x+5)]
   D = (3x+11)(-3x-5+6)
   D = (3x+11)(-3x+1)
2014-05-10T10:09:34+02:00
D= 36-(3x+5)²

1/ Développer puis réduire D.

D= 36-(3x+5)²
d = 36 -(9x² +30x +25)
d = 36 -9x² -30x -25
d = -9x² -30x +11

2/ Factoriser D.

D= 36-(3x+5)²
d = 6² -(3x+5)²
d = (6 +3x +5) ( 6-3x-5)
d =(3x +11) ( -3x +1)